Sopomenke v poimenovalnem sistemu termina celica v Slovenskem medicinskem slovarju - Jakoša, Suzana (Slavistična revija, 2021)
A linguistic analysis of terms in the extensive terminological system of the term cell in the dictionary Slovenski medicinski slovar (Slovenian Medical Dictionary) yielded a 66.9 percent share of synonyms. Within the three main types, there are 38 subtypes of synonym pairs and 33 subtypes of synonym strings. The terms in them differ according to structure, borrowed components, word-formational properties, and properties of semantic extension. Univerbation also creates synonymous terms, which are homonyms for words in general use or for terms in other professional fields. Complex words are derivatives, compounds and prefixed derivatives. In borrowed single-word terms, both components of the complex term are borrowed, whereas in synonymous terms with two or more words, the degree of the adaptation of borrowed components varies. Some borrowed single-word terms have no synonyms with two or more words, whereas some two-word terms are not univerbated despite the possibility of term formation. Borrowed single-word terms preserve the source language transfer of meaning. Synonym pairs are made of only non-borrowed terms, only borrowed ones or both borrowed and non-borrowed ones. The two longest synonym strings contain six terms and differ according to the borrowing of components, whereas the semantic-componential features are the same or different. The synonymous relation is also established in abbreviated terms and terms with eponyms. Among notable examples are synonym strings with a foreign abbreviation, a foreign unabbreviated term and an unabbreviated term adapted to Slovenian. Some terms with eponyms have no non-eponymous synonym. Despite the possibility of term formation, synonyms do not appear in all examples where they could have been created on analogy with already existing similar ones. However, the number of synonym string subtypes and particularly the number of terms in them indicate that a terminological agreement on preferred terms has not (yet) been reached in all cases.
Keywords: medicinski slovarji; slovenščina; sopomenke; sopomenski nizi; termin celica; terminološka načela